Glucose-6-phosphate dehydrogenase contributes to the regulation of glucose uptake in skeletal muscle - Robert S. Lee-Young; Nolan J. Hoffman; Kate T. Murphy; Darren C. Henstridge; Dorit Samocha-Bonet; Andrew L. Siebel; Peter Iliades; Borivoj Zivanovic; Yet H. Hong; Timothy D. Colgan; Michael J. Kraakman; Clinton R. Bruce; et al. (Elsevier, 2016)
Objective: The development of skeletal muscle insulin resistance is an early physiological defect, yet the intracellular mechanisms accounting for this metabolic defect remained unresolved. Here, we have examined the role of glucose-6-phosphate dehydrogenase (G6PDH) activity in the pathogenesis of insulin resistance in skeletal muscle. Methods: Multiple mouse disease states exhibiting insulin resistance and glucose intolerance, as well as obese humans defined as insulin-sensitive, insulin-resistant, or pre-diabetic, were examined. Results: We identified increased glucose-6-phosphate dehydrogenase (G6PDH) activity as a common intracellular adaptation that occurs in parallel with the induction of insulin resistance in skeletal muscle and is present across animal and human disease states with an underlying pathology of insulin resistance and glucose intolerance. We observed an inverse association between G6PDH activity and nitric oxide synthase (NOS) activity and show that increasing NOS activity via the skeletal muscle specific neuronal (n)NOSμ partially suppresses G6PDH activity in skeletal muscle cells. Furthermore, attenuation of G6PDH activity in skeletal muscle cells via (a) increased nNOSμ/NOS activity, (b) pharmacological G6PDH inhibition, or (c) genetic G6PDH inhibition increases insulin-independent glucose uptake. Conclusions: We have identified a novel, previously unrecognized role for G6PDH in the regulation of skeletal muscle glucose metabolism. Author Video: Author Video Watch what authors say about their articles Keywords: Glucose metabolism, Enzyme activity, Insulin sensitivity